PHYSICAL ELEMENTS OF ACCESSIBILITY FOR WAYFINDING IN AN INFORMATION DEFICIT TOURISM AREA - Laksita, Isabella Nindya; Marcillia, Syam Rachma (Nature: National Academic Journal of Architecture, 2020)
Abstrak_ Riset ini menyelidiki desa Sanggrahan sebagai pemukiman padat dan perkembangan organik yang sudah tumbuh dari waktu ke waktu menjadi pusat industri rumah tangga bakpia, sebagai tujuan wisata kuliner yang penting di Yogyakarta. Tujuan dari riset ini yaitu untuk menyelidiki pengaruh unsur-unsur fisik aksesibilitas sebagai strategi pencarian arah turis di wilayah defisit data untuk keberlanjutan kawasan pariwisata. Metode riset ini merupakan pemetaan kognitif dan kuesioner terbuka. Hasilnya menunjukkan bahwa di wilayah defisit data, turis cenderung melewati jalan dengan konektivitas yang lebih baik dari semula. Minimnya data di desa, memungkinkan turis menggunakan elemen fisik kota untuk mencari informasi aksesibilitas seperti jalan, simpul, tepi, dan landmark sebagai panduan untuk mencari jalan mencapai toko bakpia, meskipun kondisi fisik elemen dari aksesibilitas ini tidak memadai. Sebaliknya, konsep distrik digunakan oleh turis untuk mengetahui posisi mereka di distrik penjualan Bakpia Pathuk. Kata kunci: Elemen Fisik; Mencari Jalan; Desa Sanggrahan. Abstract_This study investigates Sanggrahan village as a dense and organic growth settlement that has developed over time into a center of bakpia-making home-industry, a crucial culinary tourism destination in Yogyakarta. The purpose of this research is to investigate the influence of physical elements of Accessibility to the tourists-wayfinding strategy in an information deficit area for the sustainability of the tourism area. The method of the study is cognitive mapping and open-ended questionnaires. The results show that in the information deficit area, tourists tend to go through paths with more excellent connectivity from their origins. In the village, the lack of information allows tourists to utilize the physical elements of the city for accessibility information such as paths, nodes, edges, and landmarks as guidance for wayfinding to reach the bakpia shops, even though these physical elements of accessibility conditions are inadequate. In contrast, the concept of the district is used by tourists to know their position in the Bakpia Pathuk sales district. Keywords: Physical Elements; Wayfinding; Sanggrahan Village